The enhancement of type 1 collagen expression after 10% propolis-carbonated hydroxyapatite application in periodontitis-induced rabbits - Indi Kusumawati; S. Suryono; Ahmad Syaify (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Alveolar bone defects caused by periodontitis may require regenerative therapy to restore bone structure. Propolis possesses antibacterial, anti-inflammatory and antioxidant properties, which can stimulate bone regeneration. Propolis-carbonated hydroxyapatite (CHA) material was applied during open flap debridement (OFD) in periodontitis therapy. Purpose: To analyse the effect of the application of 10% propolis-CHA after OFD on type 1 collagen expression on periodontitis-induced rabbits. Methods: Six male rabbits, aged 5–8 months, weight 1500–2000 grams, were ligated with wire and injected with Porphyromonas gingivalis lipopolysaccharide (LPS) for six weeks to induce periodontitis. The samples were divided into three groups: group A (OFD only), group B (OFD+CHA) and group C (OFD+10% propolis-CHA). To acquire 10% propolis-CHA, the CHA block was cut into 10mg and then immersed in 1ml of 10% propolis solution for 24 hours at room temperature. Decapitation was performed on the seventh and 14th day after OFD was performed on each group and microscopic slides were prepared for type 1 collagen examination. The data was analysed using a two-way ANOVA with a 95% confidence interval followed by a post hoc LSD test. Results: The type 1 collagen expression in group C (61.36±1.88 on day seven and 70.25±3.89 on day 14) was significantly different from group A (42.91±1.78 on day seven and 45.18±2.48 on day 14) and group B (43.91±5.31 on day seven and 59.63±3.27 on day 14) on both the seventh day and the 14th day (p=0.000). Conclusion: The administration of 10% propolis-CHA during OFD can increase the type 1 collagen expression in the alveolar bone of rabbits on the seventh and 14th day.